Kemahiran bahasa dan familiaritas item: Efeknya pada performa I-BNT pada suku Bali - Immanuel, Aria; van Luijtelaar, Gilles (Konsorsium Psikologi Ilmiah Nusantara, 2025)
This study investigated whether language proficiency, familiarity with the test items, years of education, age, sex, and type of residential area affect the performance of the Indonesia-adapted Boston Naming Test (I-BNT) among Balinese. 154 participants from urban and rural parts of Bali Island, varying in age and years of education, divided into three language proficiency groups, participated in this study. The results showed positive correlations between familiarity with the items and performance scores. Also, language proficiency affected the scores. However, the effect of language proficiency disappeared after accounting for age and education as covariate variables. There were no residential area effects. It can be concluded that the normative scores for the I-BNT do not need an extra adaptation beyond education and age.